Peers and Learning Motivation: The Key to Social Literacy in the Education Space - Veryani, Andi Nur; Sahabuddin, Erma Suryani; Astuti, Wiwik Wiji; Irfan, Muhammad; Amrah, Amrah (CV. Edujavare, 2024)
Learning motivation is a very influential aspect in improving student learning outcomes. The success of the teaching and learning process cannot be separated from the role of a teacher in motivating at the beginning of learning. The purpose of this research is to explore the role of peer interaction and learning motivation in enhancing students' social literacy within the educational environment, particularly at the elementary school level. The research method employed in this study is a qualitative approach, which emphasizes understanding social phenomena from the perspectives of the participants involved. The implementation of this Community Service activity focuses on providing literacy activities and the importance of peer interaction on student learning motivation, whose implementation is centered at Minasa Upa State Elementary School Makassar. This research activity greatly helped participants of this activity because participants gained additional knowledge related to literacy, the importance of peer interaction on student learning motivation, Peers and Learning Motivation: The Key to Social Literacy in the Education Space.